Simple Additive Weighting as Decision Support System for Determining Employees Salary - Setiawan, Nashrudin; D T P Nasution, M; Rossanty, Yossie; Riana Suryanti Tambunan, Anna; Girsang, Martina; T A Agus, R; Yusuf, Muhammad; Vebrianto, Rian; Nirmala Purba, Oktaviana; Fauzi, Achmad; Perdana, Surya; Nisa, Khairun (International Journal of Engineering and Technology, 2018)
Employees are seen as one of the important company assets and need to be managed and developed to support the survival and achievement of corporate goals. One form of employee organization that can be done by the company is to provide the appropriate remuneration or salary payments for employees. Increase in salary greatly affects the motivation and productivity of employees in implementing and completing the work. To determine the magnitude of the salary increase, a system is needed that can support the decision making done by the manager. Utilization of decision support system using Simple Additive Weighting (SAW) method helps managers to make quicker and more accurate decision making. This method is chosen because it is able to select the best alternative from a number of alternatives that exist based on the criteria specified. The research is done by finding the weight value for each attribute then done ranking which will determine the optimal alternative.Â Â